The Roles of Local Governments in Accommodating the Registration of SME’s Product Trademarks - Muhammad Bagus Boy Saputra; Heniyatun Heniyatun; Hary Abdul Hakim; Chrisna Bagus Edhita Praja (Amnesti Jurnal Hukum, 2021)
One of the manifestations of the government's alignment with the protection and development of MSMEs is the issuance of Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises (UU MSMEs). Protection of MSME products is protection for products consisting of goods and/or services. Every product, both goods and services, has material and immaterial wealth. Intellectual Property Rights (IPR), especially trademarks, are immaterial wealth for MSME products that need legal protection. This study aims to analyze the role of the Kebumen district government in accommodating the registration of MSME product brands. This study uses a normative juridical method with a qualitative approach. The legal materials used in this study include primary and secondary legal materials. Primary legal materials are Law Number 20 of 2016 concerning Marks and Geographical Indications, Regulation of the Regent of Kebumen Number 71 of 2016 concerning Position, Organizational Structure, Duties and Functions, as well as Work Procedures for the Department of Manpower and Cooperatives, MSME (MSME Kebumen Regent Regulation). Secondary legal materials are journaled articles, law books and websites. The results of the study indicate the role of the Kebumen Regency Government in accommodating trademark registration on MSME products in Kebumen Regency through the KUMKM Service and the KUMKM Integrated Business Service Center (PLUT). Activities carried out are in the form of socialization, consulting services, training, and assistance for MSMEs in trademark registration at the DJKI to protect the law and develop MSMEs.